Tenure Appointments for Faculty of Clinical Departments at U.S. Medical Schools: Does Specialty Designation Make a Difference?. (November 2018) - Walling, Anne; Nilsen, Kari M.
Abstract : Purpose: To describe differences and trends among clinical specialty departments in number and percentage of tenure-related appointments for full-time faculty. Method: Association of American Medical Colleges Faculty Roster annual snapshot reports were used to calculate percentages of full-time faculty holding tenure-related appointments in each of the database's 17 groupings of clinical specialty departments. Faculty numbers and percentages by track were compared to investigate trends for 2006 to 2016. Results: In the decade 2006–2016, the number of individuals on tenure-related tracks in clinical departments declined by 0.8% (276/33, 610), but those on nontenure appointments increased by 60.5% (36, 444/60, 195). The number reporting "tenure not available" rose by 58.9% (4, 467/7, 574). Currently, 62% to 82% of full-time faculty in clinical departments are on nontenure tracks. Specialties differ significantly in current percentage and in rate of change in both numbers and percentage of tenure-related appointments. In 2016, faculty on tenure-related tracks ranged from 34.5% (295/855) in public health and preventive medicine to 13.5% (654/5, 654) in family medicine. The most significant drops in percentage of tenure-related appointments in 2006–2016 were in surgery, pediatrics, and internal medicine. Conclusions: Dramatic changes in size and track distribution of faculty are occurring at significantly different rates across clinical specialty departments. The number of individuals on tenure-related tracks remains relatively stable, but the percentage of such faculty in clinical specialty departments continues to drop dramatically in almost all specialties. The growing dominance of nontenure appointments has important implications for career development and academic promotion policies and practices in all specialties.